Surgical emphysema sebagai komplikasi perawatan gigi - Fonny Dahong; Hasmawati Hasan (Journal of Dentomaxillofacial Science, 2010)
This paper reports and discusses some cases of subcutaneous emphysema whichoccurred during prolonged dental treatment procedures with high speed instrument,such as dental extraction by splitting tooth, tooth restoration, ultrasonic scaling, andhigh pressure bicarbonate cleansing. A case of emphysema was also reported aftertooth extraction without using high speed instrument. Discussion is also provided thatrelates to clinical findings and the management of subcutaneous emphysema.